Assessment of L-Band Passive Microwave Soil Moisture Retrievals Against In Situ Measurements in the North American Boreal Biome - Azza Gorrab; Oliver Sonnentag; Arnaud Mialon; Chelene C. Hanes; Juliette Ortet; Aaron A. Berg; Muhammad Umair; Alexandre Roy (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Climate change greatly impacts forest carbon and water dynamics in the boreal biome. To understand the vulnerability of the North American boreal biome to climate change disturbances, including droughts and temperature extremes, a biome-wide characterization of near-surface soil moisture (SM) is essential. SM is an important control on photosynthetic carbon dioxide uptake and the associated evaporative loss of water through transpiration. Two missions with passive microwave radiometers operating at L-band (1–2 GHz) were launched to estimate SM at a global scale: soil moisture and ocean salinity (SMOS) launched in 2009 and soil moisture active passive (SMAP) launched in 2015. In this study, we analyzed the relationships between various microwave observations [brightness temperature (TB), soil reflectivity (r), and soil moisture (SM)] derived from SMOS and SMAP with in situ SM measurements (2016–2021) over 16 sites across the boreal biome of North America. Our results show good agreement between SMAP and SMOS in terms of relationships between TB and in situ SM measurements (with a coefficient of determination R 2 > 0.7). Analysis comparing microwave variables (TB, r, and SM) and in situ SM data demonstrated considerable differences across sites and years. We observed moderate to strong correlation coefficients (R_TB > 0.5) between the TB and in situ SM data, generally when a seasonal soil drying trend emerges over the summer. However, soils with high water content and frequent precipitation input showed weaker correlations between TB and in situ SM. By analyzing the correlations between r and in situ SM data, we demonstrated that the soil effective temperature partly affects performances in terms of R_TB. Comparisons with other SMAP SM retrievals (multitemporal dual-channel algorithm and multichannel collaborative algorithm) revealed similar results in correlations and showed high spatiotemporal differences across all SM retrievals and study sites. Our findings highlight the complexity of the interactions between microwave observations and SM dynamics across the boreal biome, thus challenging the L-band passive microwave SM retrievals.